Data Management System in Geographic Information System (GIS) Application Based on The GIS Map Layout of Forest City, Tanjung Kupang, Johor - Maizatullah, Nurul Syazwani; Abu Talib, Zaihasra (Recent Trends in Civil Engineering and Built Environment, 2022)
A geographic information system (GIS) integrates computer-aided mapping with database management and research functionality. It is possible to transform any sort of information that can be provided by standard maps into digital form and handle it via GIS. This technical paper is about a data management system in GIS application based on the GIS map layout of Forest City, Tanjung Kupang, Johor. When having a huge range of data, the information of the data will be difficult to go through one at a time from the map layout. Therefore, a method needed to develop in presenting the certain data that is required which can help the architect and engineer to make a wise decision for the project. This study was also conducted to analyze and organize the geographical data and make it easier for the user to understand the information presented on the GIS map. The data was obtained from the Department of Mineral and Geoscience Malaysia (JMG) Johor. As a result, the user can get the information faster, easier, and make the right decision. This finding can be a guide in future studies in understanding and discovering more functions of GIS software in geotechnical engineering.